Cementless bendable concrete with magnesium-hydrate-silicate (M-S-H) as an alternative low CO2 binder - Koh, Wee Chen (Nanyang Technological University, 2021)
In order to mitigate the environmental issue of excessive carbon emissions from production of Portland cement, the most commonly used material in the construction industry, there has been an increase in studies with the use of reactive magnesia cement (RMC) as an alternative to Portland cement as a concrete binding material. Using sodium hexametaphosphate (SHMP) as a superplasticizer to reduce the water to binder ratio while forming magnesium-silicate-hydrate (MSH) gel can improves the engineering properties of the binder. The addition of adequate type and amount of fibers in MSH mixes as reinforcing element can improve the tensile performance of the composites and hence increase the possibility of improving the ductility of the cementitious system. The addition of fibers will help composite samples to be able to have a higher ultimate tensile strength, and the samples will also show a strain-hardening behavior where they undergo high tensile strain under increasing uniaxial tension. Strain-hardening behavior is governed by the type of fibers added, cement matrix and the fiber/matrix interface. In this project, the feasibility of MSH as an alternative binder with the inclusion of fibers have been investigated. Different fibers at varying fiber content were included into the mix as part of this study. This is to explore the possibility of making the MSH cementitious system with inclusion of fibers economical by reducing fiber content in the mix and hence reducing the overall cost of the production of MSH composites. Mechanical properties of composite samples with different fibers were tested after 28 days of curing. It is evident that with the use of polyethylene (PE) fibers and polypropylene (PP) fibers with MSH cementitious system, both sets of composites displayed improved mechanical properties with relatively high compressive strength and tensile strength. With strain-hardening behavior exhibited, multiple cracks on composite samples were observed after uniaxial tension testing. Even with the reduction of the fiber content that is incorporated into the mix, results were also desirable hence increasing the possibility of reducing the cost of fibers required for composite samples to meet desirable tensile strength.